Feminist rewriting of the Brazilian Federal Supreme Court (STF) decision on unrestricted outsourcing: Didactic-pedagogical reflections on the application of the methodology at the Federal University of Pernambuco - Corrêa Vieira, Regina Stela; Angotti, Bruna (Direito e Práxis, 2023)
https://doi.org/10.1590/2179-8966/2023/79163 The experience of feminist rewriting at UFPE took place in 2022, with a group of students and professors. RE 958.252 was chosen because it is a paradigmatic decision by the Federal Supreme Court (STF) in the labor field, changing decades of court decisions; and because it is not a topic that specifically addresses women’s work, in order to test the hypothesis that feminist lenses can alter judgments in cases that do not specifically involve a problem related to women. Meetings were held for a semester to study the techniques of feminist approaches to decisions, analyze the votes and choose the methods applied. We drafted a supplementary vote, which challenged the arguments of Supreme Court Justices who ignored gender in outsourced work, focusing on valued professions and making predominantly female, racialized and precarious categories, such as cleaning, invisible. The pedagogical experience of feminist rewriting proved to be very powerful both in identifying the extent to which law, which is supposed to be neutral, renders gender asymmetries invisible, and in encouraging the use of gender lenses for the production of truly equitable justice. Keywords: Feminist rewriting; Outsourcing; Women’s work; Didactic-pedagogical reflections.